Inclusive and Respectful Language in Scholarly Writing and Speaking. Issue 4 (July 2020) - Simpson, Kathleen Rice
Abstract : Inclusive and respectful language in manuscripts published in MCN is an important consideration in writing for the journal and editing accepted articles. As use of gender-neutral language and descriptions of race and ethnicity evolve and value-laden words are scrutinized, we will be helping authors make sure their scholarly work is appropriately presented in MCN .